Knowledge, Skills, and Abilities for Managing Potentially Volatile Police–Public Interactions: A Narrative Review - Bennell, Craig; Jenkins, Bryce; Blaskovits, Brittany; Semple, Tori; Khanizadeh, Ariane-Jade; Brown, Andrew Steven; Jones, Natalie Jennifer (Frontiers in Psychology, 2022)
We conducted a narrative review of existing literature to identify the knowledge, skills, and abilities (KSAs) necessary for officers who police in democratic societies to successfully manage potentially volatile police-public interactions. This review revealed 10 such KSAs that are frequently discussed in the literature. These KSAs include: (1) knowledge of policies and laws; (2) an understanding of mental health issues; (3) an ability to interact effectively with, and show respect for, individuals from diverse community groups; (4) awareness and management of stress effects; (5) communication skills; (6) decision-making and problem-solving skills; (7) perceptual skills; (8) motor skills related to use-of-force intervention options; (9) emotion and behaviour regulation; and (10) an ability to treat people in a procedurally just manner. Following our review, we conducted semi-structured interviews (N = 7) with researchers who specialize in police training and adult education, interactions with individuals in crisis, and racialized policing, as well as two police trainers with expertise in de-escalation and use-of-force training. These interviews confirmed the importance of the 10 KSAs and highlighted two additional KSAs that are likely to be critical: understanding the role of policing in a free and democratic society and tactical knowledge and skills. To ensure that police-public interactions are managed effectively, police trainers may want to focus on the development and evaluation of these KSAs – something that is not always done currently.